A Macroporous Magnesium Oxide-Templated Carbon Adsorbs Shiga Toxins and Type III Secretory Proteins in Enterohemorrhagic Escherichia coli, Which Attenuates Virulence - Hirakawa, Hidetada; Suzue, Kazutomo; Uchida, Motoyuki; Takita, Ayako; Kamitani, Wataru; Tomita, Haruyoshi (Frontiers in Microbiology, 2022)
Enterohemorrhagic Escherichia coli (EHEC) is one of the most common foodborne pathogens. However, no drug that prevents the severe complications caused by this bacterium has been approved yet. This study showed that a macroporous magnesium oxide (MgO)-templated carbon material (MgOC150) adsorbs Shiga toxins, and Type III secretory EspA/EspB proteins responsible for EHEC pathogenesis, and decreases the extracellular levels of these proteins. On the other hand, this material did not affect the growth of EHEC. Citrobacter rodentium traditionally used to estimate Type III secretion system-associated virulence in mice is highly virulent. The survival period of infected mice was prolonged when MgOC150 was administered. This adsorbent disturbed neither mammalian cells nor normal intestinal bacteria, such as Enterococcus hirae, Lactobacillus acidophilus, and Lactobacillus casei. In contrast, MgOC150 adsorbed antimicrobial agents, including β-lactams, quinolones, tetracyclines, and trimethoprim/sulfamethoxazole. However, fosfomycin and amikacin were not adsorbed. Thus, MgOC150 can be used with fosfomycin and amikacin to treat infections. MgOC150 is used for industrial purposes, such as an electrode catalyst, a bioelectrode, and enzyme immobilization. The study proposed another potential application of MgOC150, assisting anti-EHEC chemotherapy.